2007
DOI: 10.1590/s0034-72992007000100018
|View full text |Cite
|
Sign up to set email alerts
|

Fisioterapia na paralisia facial periférica: estudo retrospectivo

Abstract: Peri pheral facial paralysis requires specialized treatment.Physical therapy aims at reestablishing facial movements. The aim of this study was to describe and to analyze physical therapy results for individuals with peripheral facial paralysis. Study design: Retrospective study. Method: A retrospective study was carried out at the University Hospital, authorized by the Statistics and Medical File Services, from 1999 to 2003. Data are presented in descriptive form with mean and median values for numeric variab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0
23

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 11 publications
(18 reference statements)
1
2
0
23
Order By: Relevance
“…VALENÇA, VALENÇA and LIMA (18), had already pointed out the prevalence of women in their study, obtaining a similar percentage, 66,7% of the sample. GARANHANI, CAPELLI and RIBEIRO (27), in their study, also found this prevalence of women with PFP (60,8%). Total of sample N % N % N % N % Isolation Avoids leaving the house 2 50 2 33,3 4 66,7 8 50 Tries to go out, but can't 1 25 1 16,7 3 50 5 31 Avoids meeting people 3 75 1 16,7 5 83,3 9 56 Avoids talking to people 2…”
Section: Discussionsupporting
confidence: 62%
“…VALENÇA, VALENÇA and LIMA (18), had already pointed out the prevalence of women in their study, obtaining a similar percentage, 66,7% of the sample. GARANHANI, CAPELLI and RIBEIRO (27), in their study, also found this prevalence of women with PFP (60,8%). Total of sample N % N % N % N % Isolation Avoids leaving the house 2 50 2 33,3 4 66,7 8 50 Tries to go out, but can't 1 25 1 16,7 3 50 5 31 Avoids meeting people 3 75 1 16,7 5 83,3 9 56 Avoids talking to people 2…”
Section: Discussionsupporting
confidence: 62%
“…spasticity, where muscle paralysis such as facial paralysis, etc. 3,4 . The Physiotherapy finds in the electrostimulation a powerful resource to assist the process of rehabilitation of several distúrbios 5 .…”
Section: Methodsmentioning
confidence: 99%
“…O primeiro estudo médico sobre a doença é oriundo do médico Avicenna (979-1037 d.C.), que diferenciou a PFP da paralisia facial central (PFC) 1 . Charles Bell fez contribuições à história da neurologia e da anatomia, destacando o VII nervo craniano, descreveu o sinal de Bell e relacionou a hiperacusia e disgeusia como sintomas da PFP após autoobservação e observações de outros portadores 2,3. Cerca de 50% da população é acometida pela PFP de origem desconhecida, chamada paralisia de Bell 4 . Essa tem prevalência ligeiramente maior entre as mulheres.…”
Section: Introductionunclassified